2013
DOI: 10.1007/s00259-013-2594-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of CT-based and respiratory-gated PET/CT-based planning target volume (PTV) in the definition of radiation treatment planning in lung cancer: preliminary results

Abstract: Our preliminary data showed that RG-PET/CT in lung cancer can affect not only the volume of PTV but also its shape, as demonstrated by the assessment of gated PTVs outside standard PTV. The use of a gating technique is thus crucial for better delineating PTV by tailoring the target volume to the lesion motion in lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…In the context of stereotactic body radiotherapy (SBRT), it has been shown that it may be useful to derive respiratory correlated target volumes from gated (4D) PET/CT scans in addition to 4D‐CTs . However, the current common practice still is to segment the PET volume integrated over the scan time.…”
Section: Discussion Of Segmentation Limitations Dependencies and Immentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of stereotactic body radiotherapy (SBRT), it has been shown that it may be useful to derive respiratory correlated target volumes from gated (4D) PET/CT scans in addition to 4D‐CTs . However, the current common practice still is to segment the PET volume integrated over the scan time.…”
Section: Discussion Of Segmentation Limitations Dependencies and Immentioning
confidence: 99%
“…[227][228][229] In the context of stereotactic body radiotherapy (SBRT), it has been shown that it may be useful to derive respiratory correlated target volumes from gated (4D) PET/CT scans in addition to 4D-CTs. 228,230,231 However, the current common practice still is to segment the PET volume integrated over the scan time. If PET-AS algorithms are evaluated on clinical images against the activity as seen in the uncorrected PET image, endpoint a) as described in section 4.A, the potential effect of breathing motion in these images is disregarded.…”
Section: E Effect Of Motionmentioning
confidence: 99%
“…The use of respiratory gating in integrated 18 F-FDG PET/CT has been evaluated recently, especially its clinical impact on planning target volumes for radiation therapy. Preliminary results in patients with lung cancer showed that respiratory-gated 18 F-FDG PET/CT, which tailors the target volume to lesion motion, can affect the size and shape of target volumes, leading to improved delineation [40].…”
Section: Radiotherapy Planningmentioning
confidence: 99%
“…For instance, in patient 3, the centrally positioned subcarinal lymph node showed a minimal change in SUV max (2.5/2.6, a 4% gain) whereas the mediastinal lymph nodes, which have greater motion, showed a greater change (2.2/3.0, a 35% gain). SUV mean 42% (g/mL) 1.9 ± 0.5 2.4 ± 1.6 122% ± 24% 0.14 Metabolic volume 42% (mL) 2.6 ± 2.4 1.6 ± 1.4 −19% ± 34% 0.6 TLG 42% (g) 5.8 ± 7.6 3.9 ± 3.5 −5% ± 39% 0.99 SUV peak (lung) (g/mL) 0.52 ± 0.05 0.39 ± 0.14 −25% ± 19% 0.14 Lesion-to-lung SUV peak ratio 3.8 ± 2.9 6.8 ± 6.9 154% ± 41% 0.07 SUV max (patient 2: mediastinal lymph nodes, n 5 5) (g/mL) 2.7 ± 0.5 3.3 ± 0.78 123% ± 14% 0.04 Further PFV PET/CT applications can be envisioned, such as for other lesions affected by respiratory motion (breast, chest wall, liver, pancreas, bile duct and gallbladder, esophagus and stomach, spleen, heart, kidneys), for radiation oncology therapy planning (9), or for image-guided biopsies in interventional radiology. Studies investigating the ability of PFV PET/CT to discriminate between malignant and nonmalignant lesions would be desirable, as would studies using radiopharmaceuticals other than 18 F-FDG.…”
Section: Discussionmentioning
confidence: 99%